Effect of professional oral hygiene measures on the periodontal health of patients undergoing fixed orthodontic treatment - Giri, Nidhi; Giri, Dhirendra Kumar; Acharya, Anand (Journal of Kathmandu Medical College, 2023)
Background: Plaque accumulate on orthodontic appliances when proper oral hygiene is not maintained, leading to destruction of periodontal tissues. Good oral hygiene during fixed orthodontic therapy will prevent periodontal disease, which eventually will reflect final outcome of orthodontic treatment. Objectives: To find out whether professional prophylaxis midway during fixed orthodontic treatment will reduce adverse changes on periodontal health due to poor oral hygiene maintenance when compared to homecare measures only. Methods: This analytical cross-sectional study was conducted from 2022-05-06 to 2023-02-05 after institutional ethical approval among 24 patients (eight males, 16 females) undergoing fixed orthodontic treatment in Orthodontics department, Nobel Medical College. The effect of regular homecare measures only, as compared to professional prophylaxis during orthodontic treatment in addition to regular homecare on the periodontal health was evaluated on two separate visits over a nine-month period. SPSS 11.5 was used for statistical analysis. Results: This study showed improved periodontal health in “experimental group” when oral prophylaxis was done in fifth month of fixed orthodontic therapy and worsened periodontal health in “control group” during a nine-month study period. Conclusion: Significant improvement of gingival and periodontal health with an improvement in plaque control with professional prophylaxis was observed which was in accordance with most previous studies. Plaque control with professional prophylaxis after initial alignment is also of utmost importance in the maintenance of periodontal health as well as the prevention of periodontal disease during fixed orthodontic treatment. It can be considered key to good periodontal health of patients undergoing fixed orthodontic treatment.